Membangun Sekolah Bebas Bullying - Arum, Siti Khumairoh Kusuma; Aslam, Ananda; Kurnia Hadi, Adi Moh.; Hidayat, Nashiffa Thuraya; Hanafiah, Yuliana; Astuti, Rahayu; Affani Sidqi, Mochamad; Winanto, Wahyu Andika; Salsabila, Annisa Shafa; Aditriansyah, Muhammad Yoga; Saputra, Elton Krisna; Elthaufani, Lucky; Jadidah, Fikrotul (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2025)
KKN activities at Pratiwi Junior High School on May 14, 2024, aim to expand the knowledge and understanding of Pratiwi Junior High School students and increase awareness among students to prevent bullying, so as to "Build a Bullying-Free School" as the theme of KKN activities. The methods used in the implementation of KKN activities by group 1 are socialization, counseling, and panel discussions that involve learning social values by providing further information about bullying behavior from a legal perspective. The results of this KKN activity include service and empowerment to community entities in the field of education, in this case the students of Pratiwi Junior High School with socialization and counseling conducted directly by the supervisor of STIH IBLAM, namely Mrs. Fikrotul Jadidah, S.H., M.H. together with the resource person Dr. Wiend Sakti Myharto, S.H., LL.M. as a legal practitioner and welcomed enthusiastically by all Pratiwi Junior High School students along with teachers and school staff.